2006
DOI: 10.1242/jeb.02473
|View full text |Cite
|
Sign up to set email alerts
|

What explains the trot–gallop transition in small mammals?

Abstract: SUMMARY The transition from trot to gallop in quadruped mammals has been widely hypothesized to be a strategy to minimize the energetic costs of running. This view, however, has been challenged by some experimental evidence suggesting instead that this transition might be triggered by mechanical cues, and would occur when musculoskeletal stresses reach a certain critical value. All previous experiments to test those hypotheses have used relatively large species and their results, therefore, may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
(47 reference statements)
3
14
0
Order By: Relevance
“…Thus, instead of a universal criterion, different criteria have been developed (Day and Jane, 2007). It has also been suggested that certain variables should have a size-dependent interpretation (Iriarte-Diaz, 2002;Iriarte-Diaz et al, 2006). Several hypotheses different to the principle of dynamic similarity may help explain our results.…”
supporting
confidence: 54%
“…Thus, instead of a universal criterion, different criteria have been developed (Day and Jane, 2007). It has also been suggested that certain variables should have a size-dependent interpretation (Iriarte-Diaz, 2002;Iriarte-Diaz et al, 2006). Several hypotheses different to the principle of dynamic similarity may help explain our results.…”
supporting
confidence: 54%
“…Initially, these larger limb loads in the aged rats would seem to support the critical force hypothesis for symmetrical-asymmetrical gait transitions, which posits that animals change gait to reduce loading of the musculoskeletal system (Biewener and Taylor, 1986;Farley et al, 1991). However, a previous study found little support for force-motivated gait transitions in another small, crouched mammal -the degu, a caviomorph rodent (Iriarte-Diaz et al, 2006). When adult degus were injected with saline solution to experimentally increase their mass by 20%, they demonstrated no difference in gait transitions when compared with controls.…”
Section: A M Horner D W Russ and A R Bikneviciusmentioning
confidence: 87%
“…The primary alternative hypothesis for a mechanism driving gait changes is the reduction of forces applied to the musculoskeletal system [11,42,43], and, again, some support this [11] while others using the same species (horse) conclude the opposite [3]. Interestingly, a study of the small rodent Octodon degus [10] found no evidence for either hypothesis. Unlike horses [2], ptarmigans cannot be made to overlap their gaits.…”
Section: Discussionmentioning
confidence: 99%
“…horse Equus ferus caballus [2,3]; red kangaroo Megaleia rufa [4]; camel Camelus dromedaries and donkey Equus asinus [5]; ostrich Struthio camelus and emu Dromaius novaehollandiae [6,7]; and human Homo sapiens [8,9]), supporting the view that energy savings play a role in the evolution of gait changes. However, an abrupt reduction in COT with gait change is not always seen [10]. In addition, if allowed to select their gaits naturally, the trot-gallop transition in the horse [11,12] and walk -run in humans [13] occur at significantly lower speeds than would be expected if energy saving alone was being optimized.…”
Section: Introductionmentioning
confidence: 99%